A docência do professor formador de professores - Costa, Josilene Silva da (Universidade Federal de São Carlos, 2010)
Access to teaching in higher education is sought by professionals from various fields, and many start and remain in the profession, without a specific initial training or continuing to exercise it. This reality is a challenge being faced by universities and research in Education. The specificity of the work of the professor is to train professionals, including teachers and, according to the LDB, higher education institutions are responsible in training teachers for basic education. Among the various aspects involved in regard to the training of teachers, some are repeated as research topics and others are silenced. There are few discussions regarding the formation and performance of the teacher trainer of future teachers. This research builds on the work of Mizukami, Cunha, Tardif, Shulman, and its central question is: how teacher educators describe and analyze their teaching at the graduation? A study was conducted with three former teachers of Math and Letters courses of a public higher education in the State of Bahia. The goals of the research were: to understand the learning experienced by the teacher educator to develop their teaching in graduation; to analyze the priorities set by the trainers teach future teachers; to understand how the teacher trainer organizes their teaching and knowledge that mobilizes. In the methodology, interviews were conducted addressing training and professional practice of teaching and teacher trainer in graduation. The process of data analysis was based on the definition of the following focuses: learning experienced in teaching; priorities in acting with initial teacher training, knowledge and practices in the training of undergraduates; observations about the student and their education. Although it has specifics, teaching teacher trainer features many elements of approach to teaching in other contexts of education and training. This study suggests some syntheses that go toward the devaluation of teaching because, in university culture, teaching is not an activity that tends to prestige or add value to the professional teacher. Teaching is seen as arising from other activities, such as those related to research, guidance, consulting, among others. In the absence of an institutional teacher training proposal, these teachers develop a process of self formation, seeking alternatives to their needs and challenges in relation to teaching and also research. It seems that the extension in the university is not its major concern and this is just another way of fragmentation and hierarchy of knowledge and practice in university. The concerns of trainers in order to support the understanding of specific knowledge, pedagogical knowledge, contextual knowledge and professional field should be part of a project for institutional strengthening of teaching in undergraduate and professional development of trainers.
Keywords: Professores - formação; Aprendizagem profissional da docência; Formador de professores; Teacher training; Learning of teaching; Teacher teacher trainer; CIENCIAS HUMANAS::EDUCACAO